Primary small bowel adenocarcinoma: current view on clinical features, risk and prognostic factors, treatment and outcome. (2nd November 2017) - Lech, Gustaw; Korcz, Wojciech; Kowalczyk, Emilia; Słotwiński, Robert; Słodkowski, Maciej
Abstract: Small bowel adenocarcinoma (SBA) is a rare but increasing cause of gastrointestinal malignancy, being both a diagnostic and therapeutic challenge. The goal of treatment is margin negative resection of a lesion and local lymphadenectomy, followed by modern adjuvant chemotherapy combinations in selected cases. Improved outcomes in patients with SBA are encouraging, but elucidation of mechanisms of carcinogenesis and risk factors as well as improved treatment for this malignancy is very needed.